The Role of Near-Infrared Spectroscopy in Food Quality Assurance: A Review of the Past Two Decades - Marietta Fodor; Anna Matkovits; Eszter Luca Benes; Zsuzsa Jókai (Foods)
During food quality control, NIR technology enables the rapid and non-destructive determination of the typical quality characteristics of food categories, their origin, and the detection of potential counterfeits. Over the past 20 years, the NIR results for a variety of food groups—including meat and meat products, milk and milk products, baked goods, pasta, honey, vegetables, fruits, and luxury items like coffee, tea, and chocolate—have been compiled. This review aims to give a broad overview of the NIRS processes that have been used thus far to assist researchers employing non-destructive techniques in comparing their findings with earlier data and determining new research directions.